The weaver’s loom: LLMs and the fabric of global power - Ramos, M. J. (Janus: Anuário de relações exteriores, 2025)
Large Language Models (LLMs) are accelerating the restructuring of global political and economic power by amplifying capitalist "creative destruction," enabling knowledge decolonization, and reshaping democratic governance. This transformation occurs alongside the geopolitical ascent of the Global South, particularly BRICS and Shanghai Cooperation Organisation (SCO) states, which leverage sovereign AI systems to challenge Western technological hegemony. Ethnographic evidence reveals how LLMs embed cultural biases that marginalize non-Western epistemologies, while algorithmic governance models deepen democratic vulnerabilities through misinformation and state-controlled narratives. The resulting reconfiguration intensifies labor displacement, epistemic injustice, and regulatory fragmentation, demanding urgent anthropological scrutiny of AI’s societal embeddedness.